The correlation research between ground contact characteristics and rolling resistance of a tire - Woong Kim, Nam; Jung, Jinwook; Muk Cho, Haeng (International Journal of Engineering and Technology, 2019)
This study was aimed to find out the correlation between the ground contact characteristics and rolling resistance of a tire. To accomplish the goal, we used 40 sets of tires with the different rolling resistance to examined the tire ground contact characteristics and rolling resistance coefficient of the vehicles in motion. This research team assessed the tire ground contact characteristics with a dynamic contact pressure measurement system equipped with small 3-axis force sensors and 6-axis force & moment sensors, analyzing the contact patch shapes, 3-axial forces (Fx, Fy, Fz), force distribution, and vectors, which practically occur on a real track. In addition, the rolling resistance of a tire was tested according to Force Method as stipulated in ISO-28580, using the equipment (KOBE Co.). The test result showed that the magnitude of Force X among tire ground contact characteristics, which is applied in the direction a car moves, is highly correlated with rolling resistance and the rest (Force Y, Force Z, Contact Patch Shape, and vectors) turned out not significantly correlated with rolling resistance. In addition, when the characteristics of ground contact and resistance by air pressure were compared, a high correlation with Force X was reconfirmed. Moreover, coasting test confirmed the actual effect of tire rolling resistance upon the running resistance of a vehicle. In this study, we analyzed the correlation between tire ground contact characteristics and rolling resistance and experimentally derived major performance factors. In the future, we plan to conduct other experiments regarding the correlation between tire ground contact characteristics and rolling resistance in various driving environments.Â Â Â